2018
DOI: 10.1161/jaha.118.009169
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Osteonectin and Adipokine Profiles in Relation to Metabolically Healthy Obesity in Chinese Children: Findings From BCAMS

Abstract: Background The role of adipokine dysregulation in determining the metabolic fate of obesity is not well studied. We aimed to examine whether the matricellular protein osteonectin and the profiles of certain adipokines could differentiate metabolically healthy obese ( MHO ) versus metabolically unhealthy obese phenotypes in childhood. Methods and Results This study included 1137 obese children and 982 normal‐weight healthy ( NWH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 53 publications
8
21
0
Order By: Relevance
“…In addition, the leptin signaling pathways of mice in the HFD and HFD plus PSE groups are also evidently changed. The significant increase of leptin gene expression, leptin protein level in adipose tissue and plasma leptin, and reduction of leptin in the hypothalamus of mice in the HFD group (Figures 2(b) and 4(c)) are consistent with other reports [26, 27]. The results displayed in Figures 2(c), 2(e), Table 1 and Figure 4(c) suggest that PSE can improve the leptin resistance of obese mice induced by HFD and leptin/leptin receptor/AgRP/NPY and adiponectin/ADR signaling pathways involved in the antiobesity effects of PSE for obese mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the leptin signaling pathways of mice in the HFD and HFD plus PSE groups are also evidently changed. The significant increase of leptin gene expression, leptin protein level in adipose tissue and plasma leptin, and reduction of leptin in the hypothalamus of mice in the HFD group (Figures 2(b) and 4(c)) are consistent with other reports [26, 27]. The results displayed in Figures 2(c), 2(e), Table 1 and Figure 4(c) suggest that PSE can improve the leptin resistance of obese mice induced by HFD and leptin/leptin receptor/AgRP/NPY and adiponectin/ADR signaling pathways involved in the antiobesity effects of PSE for obese mice.…”
Section: Discussionsupporting
confidence: 93%
“…Adiponectin mainly targets adiponectin receptors (AdipoR1 and AdipoR2) to regulate energy metabolism and exert functions, such as antiatherogenic, anti-inflammatory, antidiabetic, and cardioprotective effect [2325]. Increased leptin gene expression in adipocytes and increased plasma leptin have been reported in obese individuals [26, 27]. The gene expression of adiponectin and plasma adiponectin in obese patients, pigs, and rodents are also significantly reduced [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, serum leptin levels were also significantly higher in MUO compared to MHO, confirming the role of this adipokine in determining insulin resistance and metabolic impairment independently of the age and BMI-z score of the population studied [38]. In our series, adiponectin levels did not differ significantly between MUO and MHO individuals, at variance with the positive correlation reported by others between serum adiponectin concentrations and the MHO phenotype in children and adolescents with overweight or obesity [39,40]. This difference might be due to different ethnicities or to the assay utilized for the determination of adiponectin (radioimmunoassay-RIA vs. enzyme-linked immunosorbent assay-ELISA).…”
Section: Discussionsupporting
confidence: 88%
“…Notable differences in the adipokine profile between MHO and MUHO subjects have been reported, which could contribute to their respective risks for T2DM and CVD. Leptin has been shown to be higher in MUHO than MHO obese Chinese children in one study (202), but was not found to differ between adult groups in several other studies (203)(204)(205). By contrast, adiponectin has consistently been shown to be higher in subjects with MHO than in those with MUHO, despite both populations having lower adiponectin than metabolically healthy lean controls (203,(205)(206)(207)(208)(209).…”
Section: Metabolically Unhealthy Obesity (Muho)mentioning
confidence: 91%